Supervision for the Improvement of Teachers Professionalism in SMKN 1 Kota Sukabumi - Sri Rahayu (Institute of Computer Science (IOCS), 2022)
Teachers play an outstanding role in deciding the path of education. It will be a qualified or not. Teachers required Academic competence, personal competence and pedagogic competence. All those competence influence their professionalism. Supervision by the principle is one of the effort teacher competence especially in the academic and pedagogic competence. Supervision is one of principle responsibility to improve teacher performance through, guiding, consulting and solving the teacher problem related to instruction. Another aim of supervision is improving teaching methodology, source of learning and helping the teacher to achieve the competency standard. The aim of this research is describe how important supervision for the development of teacher professionalism, to find out how supervision gives contribution, and to know the factors that can encourage or discourage in the process of supervision in SMKN 1 Kota Sukabumi. The methodology of this research is descriptive qualitative and the techniq of gathering the data is observation, interview, and documentation. The subject of this research are teacher and principle. There are some findings in this research such as, achieving a confirmation how important of supervision for the teacher and the principle. It is proved by the opinion of the teacher and the principle. The teacher said “ supervision make them aware of the steps of instruction’’ supervision makes them aware about the function of teaching methodology”. And the opinion of head master, “ it is important to know what is the strength and weaknesses of each teacher”, let’s improve the weaknesses and develop the strength of the teachers. Discourage factors that we found in supervision such as the hesitate of senior teacher to be supervised, some teacher lazy being supervised, some teacher feel nervous if they are supervised. and there is a psychological aspect faces by the principle to supervised because the teacher is older that the principle. The principle didn’t have enough time to supervised all the teacher and he delegated the senior teacher. In this research we come to the conclusion that supervision is the process to improve teacher performance and should be done continuously to improve the qulity of instruction.